The State, Civil Society and Democracy in Uganda - Kansiime, Noel Kiiza (American Research Journal of Humanities & Social Science (ARJHSS), 2019)
Despite increased importance and value, the civil society in the developing world has lagged behind their counterparts in the developed world in terms of performing expected functions and providing checks and balances to the central governments. In Uganda, the basic descriptive information about civil society, its size, area of activity, domestic sources of monetary and material support, and the policy framework in which it operates seem not to be available in an organized way. Civil society (CSOs) structures seem to be superficial and are shadows of the ideal concept of civil society because some of the actors have been compromised, deterred by state while others side with government when they are supposed to provide checks and balances or to promote African Charter on Democracy, Elections, and Governance (ACDEG). Therefore, this article seeks to examine the evolution and role of civil society in Uganda; how the state relates with civil society; factors that influence State-CSOs relationship in the area of advocacy and democracy and whether the theoretical concept of civil society is applicable in Uganda.